MEANING BEYOND WORDS: A SEMANTIC LOOK AT IDIOMATIC EXPRESSIONS IN EMPIRE STATE OF MIND - Lina Dismawati Singal; Steffie Mega Mahardhika (LINGUAMEDIA Journal, 2025)
This study investigates the semantic and cultural dimensions of idiomatic expressions in the song Empire State of Mind by Jay-Z and Alicia Keys. Employing a qualitative research design, the analysis draws upon Adam Makkai’s typology of idioms and integrates perspectives from cultural linguistics and semantic theory. The research identifies various idiom types—such as phrasal verbs, tournures, and figurative noun phrases—and examines their contextual meanings within the lyrical narrative. Findings reveal that these idiomatic expressions not only enhance the song’s poetic texture but also serve as symbolic vehicles for expressing cultural identity, urban resilience, and the ideals of the American Dream, particularly through the lens of New York City. The study highlights how idioms function beyond linguistic ornamentation, offering rich insights into the socio-cultural imagination embedded in popular music. Ultimately, this research contributes to the broader understanding of how language, culture, and music intersect, and presents implications for both language learning and cultural analysis in contemporary discourse.